URBAN HEAT ISLANDS IN CITY OF THE NORTHEAST SEMIARID - Silva, Juliana Maria Oliveira (2020)
The research was based on the conceptions of the Monteiro Urban Climate System (1976) and sought to identify and map the urban heat islands in the city of Crato/ Ce in two seasonal periods of the year. For this, 10 experimental points were selected and distributed in neighborhoods in the urban area of the city and air temperature data was measured with thermohygrometers installed in meteorological shelters during the months of April (rainy month) and October (dry month). From the data collection, the predominant intensity category of the intra and interurban Heat Islands for the city of Crato was that of ‘Medium magnitude’. The time that occurs the greatest intensity of the heat island is in the afternoon, 14h, with values above 5ºC of difference from one place to another. The most densely occupied neighborhoods and with low vegetation cover had the highest temperature values, while those located closer to the slope of the plateau and with more dense vegetation, the milder temperatures occurred.